Fitur Pelafalan Suprasegmental Bahasa Inggris Mahasiswa Indonesia dan Implikasi Pedagoginya - Suciati Suciati; Yuniar Diyanti (SAGA: Journal of English Language Teaching and Applied Linguistics, 2021)
This minor study aims at describing learners’ features of pronunciation in terms of their suprasegmental aspects found in their speech. Students were asked to read aloud a text entitled The Gorilla Joke from the © BBC British Council 2006. Students oral narrations were then analysed in terms of their intonation pattern and stress assignment in sentence level. A metrical analysis was also used to show how students produced their speech rhythm. The result of the analysis shows that given the same text to read students may produce various combination of intonation patterns. Students also misplaced stress within the syllables or assigned no stress at all. Based on the metrical phonology analysis, learners did not assign foot timely based on the timing units in connected speeches. The speech production is more like a broken speech. Students also neglected the morphophonemics rules in which they did not produce the appropriate allomorphs [t], [d], and [id] in the past participle words. These features bring about some pedagogical implication. Keywords: student’ pronunciation features, suprasegmental aspects